History taking in gynecology revisited: An LGBTQ perspective from Nepal - Aryal, Shreyashi; Atreya, Alok (Acta Biomedica Atenei Parmensis, 2022)
Nepal is one of the first South Asian countries to include anti discrimination laws against LGBTQ community, yet they face disparity in all sectors, including health. This group has special reproductive and sexual health needs, which has to be assessed and treated on an individual level. Most gynecologist in Nepal have not been trained to care for this vulnerable group and thus are not comfortable having them in clinical settings. History taking is essential to reach to an accurate diagnosis however, since the first year of medical school, history taking has been based on heteronormativity. To end disparities in reproductive health, learning modules for history taking for LGBTQ community is necessary for medical students, residents and for gynecologists. This would help display confidence and openness towards them and focus on individualized care.